Tiny Obturator Node Metastasis from Prostate Cancer Not Shown by FDG-PET/CT, CT, or MRI Detected by (11)C-Choline PET/CT - Kitajima, Kazuhiro (Case Rep Oncol, 2018)
We report a 65-year-old male with histopathologically proven prostate cancer and multiple pelvic node metastases using a robotic-assisted radical prostatectomy procedure plus extended pelvic lymph node dissection. Positron emission tomography (PET) scan findings demonstrated a moderate accumulation of (11)C-choline in a metastatic left obturator node sized 8 × 8 mm, though only a faint uptake of fluorodeoxyglucose (FDG) was noted. (11)C-choline PET/computed tomography (CT) may be useful for the diagnosis of a tiny metastatic lymph node not demonstrated by CT, magnetic resonance imaging, or FDG-PET/CT and to determine the need for an extended pelvic lymph node dissection.